Issues of training specialists in establishing the Fergana Valley irrigation system (50-70th of the 20th century) - Ruzikulova Maftuna Yuldashevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted preparing specialists to the irrigation system of Ferghana valley and its issues in 50-70-years XX century by the helping scientific literatures and primary resources.